Study and analysis of safety management system at granite mining industry using non-conventional machining process. (2021) - Thirumalai, R.; Seenivasan, M.; Sivakumar, A.
Abstract: In granite industries non-conventional machining process are employed for the extraction of the work material. This involves safety precautions in the materials industry and Safety management system is one of the essential element that can save lots of human lives at granite mines. This research paper is based on the safety management system on granite mines including health standards of the employees. The researcher will evaluate significant literature review based on the safety protocols and safety measurements. In this manner, critical research methods will be analyzed in the research methodology for developing a successful research paper. Moreover, a field survey along with results is also analyzed. Finally, the researcher provides suggestion regarding safety management.